2013
DOI: 10.1016/j.tim.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and geographic expansion of zoonotic arboviral diseases: mechanisms and potential strategies for prevention

Abstract: Arthropod-borne viruses (arboviruses) mainly infect people via direct spillover from enzootic cycles. However, dengue, chikungunya, and yellow fever viruses have repeatedly initiated urban transmission cycles involving human amplification and peridomestic mosquito vectors to cause major epidemics. Here, I review these urban emergences and potential strategies for their prevention and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 15 publications
(20 reference statements)
2
171
0
8
Order By: Relevance
“…In order to reduce disease burden, reductions in urban mosquito-human transmission seem to be the only option [83]. Since 80 % of infected individuals are asymptomatic, mosquito bites avoidance such as personal protection helps to disrupt human-to-mosquito-to-human transmission cycles [76].…”
Section: Reduction Of Urban Mosquito-human Transmissionmentioning
confidence: 99%
“…In order to reduce disease burden, reductions in urban mosquito-human transmission seem to be the only option [83]. Since 80 % of infected individuals are asymptomatic, mosquito bites avoidance such as personal protection helps to disrupt human-to-mosquito-to-human transmission cycles [76].…”
Section: Reduction Of Urban Mosquito-human Transmissionmentioning
confidence: 99%
“…Yellow fever (YF) virus (YFV) is a major public health problem in Africa and South America, with a history of causing epidemics worldwide including the U.S. (Ishikawa et al, 2014; Paessler and Walker, 2013; Weaver, 2013). The World Health Organization estimates 200 000 cases of YF and 30 000 deaths worldwide annually.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic and epidemiological analysis supports a model of YFV emergence that is dependent upon both the presence of competent mosquito vectors and nonhuman primate reservoir hosts (Grard et al, 2010; Quaresma et al, 2013). The dynamic ecological and climatic changes associated with international travel, trade, and urbanization increase the potential of YF spread to previously non-endemic regions of the world (Weaver, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic studies have revealed that these early CHIKV strains form three major, geographically distinct lineages: the West African enzootic, East/Central/South African (ECSA) enzootic, and Asian endemic/epidemic lineages (11). The enzootic lineages involve sylvatic transmission by arboreal Aedes mosquitoes among nonhuman primates with occasional spillover to humans, while the endemic/epidemic lineages are transmitted human to human by A. aegypti and, recently, A. albopictus mosquitoes in peridomestic settings (10,12). Bayesian coalescent analysis has estimated that the Asian and ECSA lineages diverged about 100 years ago, although it is unclear exactly when the Asian lineage was introduced from Africa (13).…”
mentioning
confidence: 99%